Chlorido(2-{1-[(2-morpholino-eth-yl)imino]-eth-yl}phenolato-κN,N',O)copper(II). - Ikmal H, N.A.; Suleiman G, N.; Khaledi, H.; Mohd A, H. (International Union of Crystallography, 2010)
In the title compound, [CuCl(C(14)H(19)N(2)O(2))], the Cu(II) ion is four-coordinated by one deprotonated N,N',O-tridentate Schiff base and one chloride ion in a distorted square-planar geometry. In the crystal, adjacent mol-ecules are linked via C-H⋯Cl and C-H⋯O inter-actions, forming infinite layers parallel to the (100) plane. The structure was determined from a non-merohedrally twined crystal [twin ratio 0.777 (3):0.223 (3)].